2019
DOI: 10.2134/agronj2019.03.0225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trinexapac‐Ethyl, Surfactant, and Nitrogen Fertilization on Bermudagrass Water Use

Abstract: Persisting drought conditions in California are limiting water allocation for golf course irrigation. A study was conducted at the University of California, Riverside to determine if products including trinexapac-ethyl (TE), a surfactant (Revolution), and nitrogen (N) fertilizer [Gro-Power (5-3-1); SeaBlend (12-4-5) + StressRX (6-0-2) + XP Extra Protection (5-0-0); YaraLiva (15.5-0-0); Turf Royale (21-7-14); each applied at 25 g N m -2 yr -1 ) could enhance quality of 'Princess 77' bermudagrass (Cynodon dactyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…Our results are consistent with those of Hays, Barber, Kenna, and McCollum (1991) and Schiavon et al. (2019), who found no correlation between root morphology in the first 30 cm of soil and visual quality of bermudagrass. Although increased root length is associated with drought avoidance in bermudagrass (Zhang et al., 2019; Zhou, Lambrides, & Fukai, 2014; Zhou et al., 2018), periodic, short‐term droughts never hindered the quality of nonirrigated Yukon in northern Italy (Rimi et al., 2013; Schiavon et al., 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with those of Hays, Barber, Kenna, and McCollum (1991) and Schiavon et al. (2019), who found no correlation between root morphology in the first 30 cm of soil and visual quality of bermudagrass. Although increased root length is associated with drought avoidance in bermudagrass (Zhang et al., 2019; Zhou, Lambrides, & Fukai, 2014; Zhou et al., 2018), periodic, short‐term droughts never hindered the quality of nonirrigated Yukon in northern Italy (Rimi et al., 2013; Schiavon et al., 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, no increases in quality or density were reported for ‘Tifway’ hybrid bermudagrass when N rates exceeded 200 kg N ha −2 yr −1 (Johnson, Carrow, & Burns, 1987). Although higher turfgrass quality, clippings dry biomass, and weekly growth rate were documented with increasing N rates (Volterrani, Grossi, Foschi, & Miele, 2005), the source of N does not seem to influence well‐watered bermudagrass performance during the summer months (Schiavon, Orlinski, Petelewicz, Pudzianowska, & Baird, 2019; Serena, Schiavon, Sallenave, & Leinauer, 2018). These studies concluded that investigating the response of bermudagrasses to a wider range of N applications rates was necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, less soil moisture variability was observed from all wetting agents tested in this study. This finding is supported by Schiavon et al (2014) and Schiavon et al (2019) who demonstrated greater uniformity of soil moisture was found in plots treated with a wetting agent. Likewise, wetting agent and irrigation treatments exhibited no effects on proline accumulation in 2018.…”
Section: Discussionsupporting
confidence: 58%
“…Its results might be affected by factors beyond plant water status, such as leaf cell constituents or shadows in the canopies (Bremer, Lee, Su, & Keeley, 2011). Furthermore, wetting agents had no effect on bermudagrass fall color retention, and this finding is in agreement with Schiavon et al (2019). The effect of wetting agents may be negligible since fertilization, cultural practices, and other factors could also affect fall color retention.…”
Section: Discussionsupporting
confidence: 56%
“…A previous study showed that mixing a surfactant with PM will increase cover and decrease irrigation in bermudagrass [ Cynodon dactylon (L.) Pers.] (Schiavon, Orlinski, Petelewicz, Pudzianowska, & Baird, 2019; Serena, Sportelli, Sevostianova, Sallenave, & Leinauer, 2018). Fagerness and Penner (1998) showed that mixing a surfactant with an older formulation of TE called Primo increased the uptake and absorption of the active ingredient.…”
Section: Introductionmentioning
confidence: 99%